2006
DOI: 10.1109/tbme.2006.878067
|View full text |Cite
|
Sign up to set email alerts
|

Development and assessment of methods for detecting dementia using the human electroencephalogram

Abstract: This paper makes an outline case for the need for a low-cost, easy to administer method for detecting dementia within the growing at risk population. It proposes two methods for electroencephalogram (EEG) analysis for detecting dementia that could fulfil such a need. The paper describes a fractal dimension-based method for analyzing the EEG waveforms of subjects with dementia and reports on an assessment which demonstrates that an appropriate fractal dimension measure could achieve 67% sensitivity to probable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
105
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 29 publications
2
105
0
2
Order By: Relevance
“…Numerous studies have been conducted on the CAD system to deal with EEG changes associated with dementia. The researchers developed CAD methods to identify the degree of severity of dementia, and some studies support the possibility for EEG to detect dementia in early stages [46][47][48][49][50]. For example, Henderson et al [51] detected early dementia presence in EEGs with high sensitivity and specificity [46,51].…”
Section: Dementia Alzheimer's and Parkinson Diseases Diagnosismentioning
confidence: 99%
“…Numerous studies have been conducted on the CAD system to deal with EEG changes associated with dementia. The researchers developed CAD methods to identify the degree of severity of dementia, and some studies support the possibility for EEG to detect dementia in early stages [46][47][48][49][50]. For example, Henderson et al [51] detected early dementia presence in EEGs with high sensitivity and specificity [46,51].…”
Section: Dementia Alzheimer's and Parkinson Diseases Diagnosismentioning
confidence: 99%
“…For example, a chaos based estimate for the uncertainty of an EEG signal, namely the fractal dimension of the waveform (a measure of self similarity at different scales), was reported in Henderson et al (2006) as being suitable for the identification of subjects with Alzheimer's disease (AD). Watanabe et al (2003) showed that the Lempel-Ziv (LZ) complexity (Ziv and Lempel, 1978), which is a measure of "symbolic complexity", could be successfully applied to EEG waveforms to distinguish between different gross brain states and different patterns of EventRelated Potentials (ERPs).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, spectral features have been used to quantify the abnormalities in the spectra of AD patients' EEGs and MEGs [3,[6][7][8]. Additionally, nonlinear analysis methods can provide useful information about the brain dynamics in this dementia [4,5,[8][9][10]. Nevertheless, it is desirable to develop novel strategies to help in AD detection from the analysis of the electromagnetic brain activity [9,11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, nonlinear analysis methods can provide useful information about the brain dynamics in this dementia [4,5,[8][9][10]. Nevertheless, it is desirable to develop novel strategies to help in AD detection from the analysis of the electromagnetic brain activity [9,11,12]. Techniques based on spatial filtering can help to achieve this goal, as these algorithms offer additional perspectives to examine EEG and MEG signals [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%